Pengaruh Kualitas Pelayanan dan Kepercayaan Pelanggan Terhadap Loyalitas Pelanggan Grooming Hewan Kota Medan - Panjaitan, Joy Lonner; Royani, Ida (Mahesa Research Center, 2025)
This study examines the influence of service quality and customer trust on customer loyalty of Medan grooming consumers. This study uses a quantitative research type because the symptoms of the observation results are converted into numbers that are analyzed using statistics. Quantitative research requires researchers to explain how variables affect other variables. This study uses associative research, namely research to determine the relationship between two (or more) variables. The relationship between variables in the study will be analyzed using relevant statistical measures of the data to test the hypothesis. Sugiyono's associative research (2019) is a study that aims to determine the relationship between two or more variables. The results of the study show that service quality has a positive and significant effect on the customer loyalty of Medan Grooming consumers. Customer trust has a positive and significant effect on customer loyalty of Medan Grooming consumers. In addition, service quality and customer trust have a positive and significant effect on the customer loyalty of Medan Grooming consumers.